An Efficient Affinity Propagation Clustering Technique - Snehlata Yadav (International Journal of Advanced Science and Technology, 2020)
Clustering Problem is the important technique that has been addressed several times. It has importance fordata analysis in enormous application domains. There are numerous clustering methods available in theliterature, this paper addresses a Feature based Affinity Propagation (FBAP) clustering method that improvesthe clustering solution. It increases intra cluster similarity by applying weighted feature to the data point beforedecision making process in cluster assignment. Intrusion detection has been the point of attraction for manyresearchers from last decades so the effectiveness of the algorithm is demonstrated on DARPA’s KDD Cup’99training dataset.